High Speed Digital Circuits for Medical Communication; the MINCS-UH Project - Kiuchi, T.; Takahashi, T. (Methods of Information in Medicine, 2000)
In Japan, a high speed, bidirectional digital satellite communication system called Medical Information Network by Communications Satellite for University Hospitals is currently available in 30 national universities, and many programs, including clinical conferences, lectures and tutorials, have been broadcasted. Its characteristics are: (1) a state-of-the-art digital high-definition television system, (2) excellent security protection using digital encryption (3) bidirectional communications using two satellite circuits simultaneously, and (4) easy operability. High-quality motion images, and security protection mechanisms are essential for use in clinical medicine.
Keywords: Communication Satellite; Cryptography; High-Definition Television